2013
DOI: 10.1111/j.1469-0691.2012.03961.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli clonal group A causing bacteraemia of urinary tract origin

Abstract: Escherichia coli clonal group A (CgA) causes disease in humans. This is the first study investigating the prevalence of CgA among E. coli from non-urine, extraintestinal infections in a northern European country. E. coli blood (n = 196) and paired urine (n = 195) isolates from the same patients with bacteraemia of urinary tract origin were analysed. The isolates were collected from January 2003 through May 2005 at four hospitals in Copenhagen, Denmark. Pulsed-field gel electrophoresis (PFGE) patterns, antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…The statistical power in this evaluation was low, and may not be comparable to a level of 15% of isolates found in a study of E. coli bacteremia of urinary tract origin [35]. Our findings support the insight that also phylogroup A E. coli can cause severe infection from a variety of sources, including urinary tract origin.…”
Section: Mtc-h (11 Strains)supporting
confidence: 73%
“…The statistical power in this evaluation was low, and may not be comparable to a level of 15% of isolates found in a study of E. coli bacteremia of urinary tract origin [35]. Our findings support the insight that also phylogroup A E. coli can cause severe infection from a variety of sources, including urinary tract origin.…”
Section: Mtc-h (11 Strains)supporting
confidence: 73%
“…By MLST, CgA strains were subsequently found to belong to the ST69 complex [56]. ST69 strains belong to ECOR phylogenetic group D and serogroups that include O11, O15, O17, O44, O73, O77, O86, O125ab, and O25b [11,14,[56][57][58]. The prototype ST69 strain (O11; ATCC BAA-457) has the VF profile shown in Table 2 [59,60].…”
Section: St69 Complex (Clonal Group a (Cga))mentioning
confidence: 99%
“…Since the first recognition in 1999, CgA and ST69 strains have been reported from many other regions of the world from both community-acquired and healthcare-associated UTIs and BSIs [8,57,[61][62][63][64][65]. Most strains are multidrug-resistant, and typically harbour a single arrangement of a gene cassette (dfrA17-aadA5) encoding dihydrofolate reductase and aminoglycoside adenyltransferase, respectively, on a class I integron [66,67].…”
Section: St69 Complex (Clonal Group a (Cga))mentioning
confidence: 99%
“…The authors suggested this specific genotype to be uncommon and proposed assignment to the phylogenetic group B2 because of the multi-locus sequence type (MLST), pathogenicity-associated islands and quinolone susceptibility (Mendonça et al, 2011). The aim of our study was to investigate the occurrence of the yjaA/ Clermont et al (2000) (Jakobsen et al, 2010b;Skjøt-Rasmussen et al, 2012). Of the 1355 isolates, 205 belonged to phylogroup B1, of which four presented the yjaA/TspE4.C2 profile.…”
mentioning
confidence: 99%
“…To understand their virulence potential, the four isolates were screened for the presence of 23 virulence-associated genes (VAGs) with known or suspected relevance to the pathogenesis of ExPEC (Table 1) (Ejrnaes et al, 2011;Skjøt-Rasmussen et al, 2012). The pig isolate harboured two VAGs, whereas the meat isolate harboured five VAGs and the human isolates harboured the same 12 VAGs (Table 1).…”
mentioning
confidence: 99%